Assessing the Effectiveness of Conservation Stocking for the Endangered White’s Seahorse Hippocampus whitei - Harasti, David; Brennan, Mitchell; Booth, David J. (Frontiers in Marine Science, 2022)
The White’s seahorse Hippocampus whitei was listed as an Endangered species in 2020 on Australian state and federal legislation, as a result of population declines across its range attributed to habitat loss over the past decade. A captive-bred reintroduction program has been implemented as a possible management tool for species recovery, however, the viability of such a reintroduction program for seahorses has not been assessed to date. This study implemented a pilot captive-breeding program using adult H. whitei from Sydney Harbour, Australia, as brood stock. A total of 90 captive-bred seahorses were released into the wild on two different artificial habitat types (“seahorse hotels” and protective swimming net). Following release, a monthly post-release monitoring program was implemented for 12 months that involved underwater visual census surveys of the tagged seahorses. Sightings of captive-bred seahorse numbers were found to gradually decline over the 12-month period, with fewer seahorses found on the swimming net compared to the seahorse hotels and higher resighting probability of captive-bred animals on the seahorse hotels. After 12 months, 20% of the captive-bred seahorses were detected on the seahorse hotels, whilst four individuals were still observed 19 months after release. Only 2% of captive-bred seahorses were observed on the swimming net after 12 months, with two individuals still detected on the net after 18 months. Nine of the captive-bred seahorses were found to reproduce in the wild, with two individuals observed mating with the wild population. This pilot study indicates that captive-bred seahorses can survive for up to 19 months in the wild, as well as contribute to local population recovery through reproductive success. However, while conservation stocking shows promise as a potential management tool to assist with threatened seahorse species recovery, there are several factors such as existing threats to the species that need to be addressed before such a program is implemented.